Lived experiences deaf learners with hearing teachers - Trinidad, John Paulo Santos (Animo Repository, 2022)
Teachers play a major role in educating students. For teachers of Deaf and Hard-of-hearing students it can be a little more challenging. But what do the Deaf and hard-of-hearing students have to say about their hearing teachers? This sequential mixed method phenomenological study sought to answer the following questions: (1) What are the most common issues that deaf and hard of hearing (DHH) students have with hearing teachers? (2) What are the lived experiences of deaf and hard-of-hearing students with hearing teachers? (3) What do these students feel contributed to those experiences? Forty-four (44) deaf and hard-of-hearing high-school graduates were asked to answer a questionnaire and 9 of them were asked in an in-depth interview. They reflected on the good and bad experiences they went through with hearing teachers, while they were in their elementary and high school years. Results indicated that although some teachers, showed compassion, and supportive attitude towards deaf and hard-of-hearing students, the lack of awareness of Deaf culture made it a challenge for both students and teachers, with problems ranging from the lack of skills in doing sign language, to issues of unequal treatment of students. It is suggested that understanding the nature of the student entails gaining a better discernment of their language, culture, and values. This understanding will assist hearing teachers in providing greater classroom support for the deaf and hard of hearing students.